Perlindungan Hukum Terhadap Hak Milik Atas Tanah Yang Hilang Akibat Abrasi - Koswara, Nur Salsabila; Djaja, Benny; Sudirman, M (PSHPM Untag Semarang, 2025)
A natural phenomenon known as abrasion can eliminate or reduce land area, especially in coastal areas. The purpose of this research is to find out the legal protection of land ownership rights lost due to abrasion. This article will discuss the legal protection of property rights to land lost due to abrasion, both from the point of view of agrarian law and the practice of Notaries. Legislation, cases, and concepts are used in normative juridical research. The results of the study show that there is a need for more specific and clear arrangements regarding soil abrasion in Indonesian agrarian law, given the uncertainty faced by landowners. Legal protections should be clearly formulated to determine the status of land ownership lost to abrasion and the appropriate mechanism for filing claims or obtaining compensation.Â Likewise, the role of Notaries cannot be denied, considering that notaries function as a liaison in legal processes related to land. By providing legal certainty through authentic documents, notaries can help reduce disputes that arise due to loss of property rights.